Expression of Nav1.5 in the pathogenesis of temporal lobe epilepsy - Zhou, Yi; Luo, Zhaohui; Bi, Fangfang; Li, Jing; Xiao, Bo (Cellular and Molecular Biology, 2019)
To investigate the expressions of Nav1.5 mRNA at different time points in a rat model of temporal lobe epilepsy (TLE), and to assess the potential contribution of Nav1.5 to epileptogenesis. Male Sprague-Dawley rats (72) weighing 230 to 250 g were used for this study. They were randomly assigned to six groups (12 rats/group): control and five TLE groups. The TLE groups were day 1 (acute period), days 7 and 14 (latent period), and days 30 and 60 (chronic period). With the exception of control, epilepsy was induced in the rats with an intraperitoneal (i.p.) injection of aqueous solution of lithium chloride 18 h prior to pilocarpine injection (i.p.) at a dose of 125 mg/kg body weight (b.wt). Rats in the control group were injected i.p. with 0.9 % sodium chloride (125 mg/kg b.wt.) in place of pilocarpine. A total of 84 out of 112 rats developed status epilepticus (SE). The expression of Nav1.5 in the brains of rats was assessed using quantitative real-time polymerase chain reaction (qRT-PCR), immunohistochemistry and Western blot analysis. The expressions of Scn5a mRNA in the hippocampus during the latent and chronic periods were significantly higher than in the control group (p < 0.05), but there were no significant differences in the corresponding expressions between the two different time points in the latent and chronic period groups (p > 0.05). The expression peaked 30 days post-SE, and was sustained for 60 days. There was no significant difference in the expression of Scn5a mRNA in the acute group, when compared to control. Immunohistochemical staining showed that expression levels of Nav1.5 in the CA3 region during latent and chronic periods were significantly higher than those in control group (p < 0.05), and the expressions peaked at day 30. However, there was no significant difference in the expression of Nav1.5 in the latent group, relative to the chronic period group. These results show that Nav1.5 might be involved in the pathogenesis of TLE.